Bioprinting of mineralized constructs utilizing multichannel plotting of a self-setting calcium phosphate cement and a cell-laden bioink. (27th July 2018) - Ahlfeld, Tilman; Doberenz, Falko; Kilian, David; Vater, Corina; Korn, Paula; Lauer, Günter; Lode, Anja; Gelinsky, Michael
Abstract: Due to their characteristic resemblance of the mineral component of bone, calcium phosphates are widely accepted as optimal bone substitute materials. Recent research focused on the development of pasty calcium phosphate cement (CPC) formulations, which can be fabricated into various shapes by low-temperature extrusion-based additive manufacturing, namely 3D plotting. While it could be demonstrated that sensitive substances like growth factors can be integrated in such printed CPC scaffolds without impairment of their biological activity live cells cannot be suspended in CPC as they may not be functional when enclosed in a solid and stiff matrix. In contrast, 3D bioprinting of soft cell-laden hydrogels (bioinks) enables the fabrication of constructs with spatially defined cell distribution, which has the potential to overcome problems of conventional cell seeding techniques—but such objects lack mechanical stability. Herein, we combine 3D plotting of CPC and bioprinting of a cell-laden bioink for the first time. As model bioink, an alginate-methylcellulose blend (alg/mc) was used, previously developed by us. Firstly, a fabrication regime was established, enabling optimal setting of CPC and cell survival inside the bioink. As the cells are exposed to the chemical changes of CPC precursors during setting, we studied the compatibility of the complex system of CPC and cell-laden alg/mc for a combined extrusion process and characterized the cellular behavior of encapsulated human mesenchymal stroma cells within the bioink at the interface and in direct vicinity to the CPC. Furthermore, biphasic scaffolds were mechanically characterized and a model for osteochondral tissue grafts is proposed. The manuscript discusses possible impacts of the CPC setting reaction on cells within the bioink and illustrates the advantages of CPC in bioprinting as alternative to the commonly used thermoplasts for bone tissue engineering.